The comparison of the Sensitivity Value of Gold Nanoparticles (AuNPs) between ANTAM and Commercial Gold Sources in the Detection of SARS-CoV-2: A Preliminary Study - Istianah, Istianah; Vidiawati, Agustina; Alfiyan, Akhmad Irfan; Andreani, Agustina Sus (Universitas Jenderal Soedirman, 2024)
Gold nanoparticles (AuNPs) have been developed as a colorimetric sensor to detect SARS-CoV-2 with surface modification using N-ethyl-N′-(3-(dimethylamino)propyl) carbodiimide/N-hydroxysuccinimide (EDC/NHS) and angiotensin-converting enzyme II (ACE-2). The gold sources used in the synthesis are produced by PT Aneka Tambang Indonesia (ANTAM) and commercial gold nanoparticles (AuNPs). This study compares the sensitivity values of ANTAM gold sources and commercial AuNPs in detecting SARS-CoV-2. The AuNPs-ANTAM detection test against the SARS-CoV-2 resulted in LoD and LoQ values of 5.38 ng/mL and 17.92 ng/mL, in the linearity curve range of 10 – 50 ng/mL, respectively. LoD and LoQ values of commercial AuNPs for detecting SARS-CoV-2, respectively, are 6.69 ng/mL and 22.31 ng/mL in the linearity curve range of 10 – 50 ng/mL. Based on the LoD and LoQ values, AuNPs-ANTAM is more sensitive than commercial AuNPs in detecting SARS-CoV-2 over the same range of linearity curves. Keywords: ACE-2, colorimetry sensor, EDC/NHS, gold nanoparticles, SARS-CoV-2, surface Modifications